2019
DOI: 10.21873/anticanres.13816
|View full text |Cite
|
Sign up to set email alerts
|

G3BP1 Depletion Increases Radiosensitisation by Inducing Oxidative Stress in Response to DNA Damage

Abstract: Background: RAS GTPase-activating proteinbinding protein ( G3BP1) is an RNA-binding protein that is essential for assembling stress granules. Many functions related to the survival and progression of cancer have been reported. The current study aimed to investigate the role of G3BP1 in radio-sensitisation of cancer cells. Materials and Methods: Radiation sensitivity and chemosensitivity were analysed in A549 and H460 cells transfected with G3BP1 siRNAs, and N-acetyl-L-cysteine (NAC) was used to elucidate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
0
15
0
2
Order By: Relevance
“…MS-based protein interactome studies demonstrated that SLU7 interacts with components of the SGs in unstressed conditions, both in vivo and in vitro. Moreover, we found that SLU7 is necessary to secure SG formation upon stress induction, as SLU7 is required to maintain the expression of the SG core components G3BP1 and USP10 (28), which in turn also have antioxidant capacity (30,31). While the specific mechanisms involved in the stabilization of SG components by SLU7 remain to be fully elucidated, we revealed that USP10 antioxidant function controls HNF4 stability, and that upon liver damage SLU7 haploinsufficiency results in USP10 downregulation.…”
Section: Accepted Articlementioning
confidence: 86%
“…MS-based protein interactome studies demonstrated that SLU7 interacts with components of the SGs in unstressed conditions, both in vivo and in vitro. Moreover, we found that SLU7 is necessary to secure SG formation upon stress induction, as SLU7 is required to maintain the expression of the SG core components G3BP1 and USP10 (28), which in turn also have antioxidant capacity (30,31). While the specific mechanisms involved in the stabilization of SG components by SLU7 remain to be fully elucidated, we revealed that USP10 antioxidant function controls HNF4 stability, and that upon liver damage SLU7 haploinsufficiency results in USP10 downregulation.…”
Section: Accepted Articlementioning
confidence: 86%
“…G3BP1 enhances the resistance of sunitinibresistance RCC (128). This suggests that targeting G3BP1 may prove to be an effective therapeutic strategy for RCC (129).…”
Section: G3bp Regulates Kidney Cancermentioning
confidence: 98%
“…G3BP1 depletion increases Bax protein levels and consequently cell apoptosis, therefore identifying G3BP1 as a potential target for sensitizing cancer cells to chemotherapy. Moreover, G3BP1 depletion sensitizes human NSCLC cell lines to radiationinduced cell death by impairing both ROS scavenging and DNA repair [68].…”
Section: Open Accessmentioning
confidence: 99%